2012
DOI: 10.1093/ije/dys003
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of environmental factors: persistent pollutants and nutrients correlated with serum lipid levels

Abstract: Background Both genetic and environmental factors contribute to triglyceride, low-density lipoprotein-cholesterol (LDL-C), and high-density lipoprotein-cholesterol (HDL-C) levels. Although genome-wide association studies are currently testing the genetic factors systematically, testing and reporting one or a few factors at a time can lead to fragmented literature for environmental chemical factors. We screened for correlation between environmental factors and lipid levels, utilizing four independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
129
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 85 publications
8
129
0
1
Order By: Relevance
“…20−22 Meanwhile, it is reported that serum PFOA in occupational exposed people was associated with total cholesterol (CHOL), total bilirubin, serum aspartate transaminase (AST), and thyroid parameters. 23,24 However, the findings of statistically significant associations between PFAS exposure and clinical biomarkers vary between different studies, 25,26 and so far the evidence for human health effects as a consequence of PFAS exposure remain largely inconclusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20−22 Meanwhile, it is reported that serum PFOA in occupational exposed people was associated with total cholesterol (CHOL), total bilirubin, serum aspartate transaminase (AST), and thyroid parameters. 23,24 However, the findings of statistically significant associations between PFAS exposure and clinical biomarkers vary between different studies, 25,26 and so far the evidence for human health effects as a consequence of PFAS exposure remain largely inconclusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While the analyses conducted herein have been used to search for associations in chronic diseases and biomarkers such as serum lipids (Patel et al ., 2012), we are not aware of any published work focusing on human fecundity or related impairments such as conception delay or pregnancy loss. To this end, we cannot interpret our findings in the context of earlier work, but data‐driven techniques can be extended to include emerging biomarkers of male fecundity, such as sperm function tests or in vitro capacitation tests (Wang & Swerdloff, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Prioritization and/or hypothesis generation research aimed at delineating the prognostic role of semen phenotypes for male fecundity may benefit from the use of emerging methods capable of systematically analysing many factors to identify environmental exposures and phenotypes associated with disease (Patel & Ioannidis, 2014). Examples of analogous data‐driven investigations included searches of environmental or behavioral factors associated with type 2 diabetes (Patel et al ., 2010), serum lipids (Patel et al ., 2012), blood pressure (Tzoulaki et al ., 2012), endometrial cancer (Merritt et al ., 2015), all‐cause mortality (Patel et al ., 2014), family income (Patel et al ., 2015) and pre‐term birth (Patel et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A few recent papers aim to examine the problem more generally as opposed to single exposure-effect associations and have had some success in generating novel hypotheses. Patel et al [26,27,28] used multiple regression models to screen several exposures for possible effects on a targeted health marker. This approach enabled ranking of the different exposures within and across NHANES cycles using a false discovery rate corrected p-value.…”
Section: Related Workmentioning
confidence: 99%
“…They also don't easily allow comparisons and ranking between different independent variable(s) unless an approach like Patel et al [26,27,28] is taken. In the case of missing or non-co-occurring variables it is not possible to estimate the common effects co-exposures may have.…”
Section: Related Workmentioning
confidence: 99%